Novel Insights Into Immune Systems of Bats - Banerjee, Arinjay; Baker, Michelle L.; Kulcsar, Kirsten; Misra, Vikram; Plowright, Raina; Mossman, Karen (Frontiers in Immunology, 2020)
In recent years, viruses similar to those that cause serious disease in humans and other mammals have been detected in healthy bats. These include filoviruses, paramyxoviruses and coronaviruses that cause severe diseases such as Ebola virus disease, Marburg haemorrhagic fever and severe acute respiratory syndrome (SARS) in humans. The evolution of flight in bats seem to have selected for a unique set of antiviral immune responses that control virus propagation, while limiting self-damaging inflammatory responses. Here, we summarize our current understanding of antiviral immune responses in bats and discuss their ability to co-exist with emerging viruses that cause serious disease in other mammals. We highlight how this knowledge may help us to predict viral spillovers into new hosts and discuss future directions for the field.